Slow 0.1 Hz Breathing and Body Posture Induced Perturbations of RRI and Respiratory Signal Complexity and Cardiorespiratory Coupling - Matić, Zoran; Platiša, Mirjana M.; Kalauzi, Aleksandar; Bojić, Tijana (Frontiers in Physiology, 2020)
Revealing the physiological background of nonlinear operating mode of cardiorespiratory oscillators is the fundamental question for understanding cardiorespiratory homeodynamics and a step towards the understanding of neurocardiovascular diseases. We investigated on 20 healthy human subjects the change of Detrended Fluctuation Analysis (α1RRI, α2RRI, α1Resp, α2Resp), Multiple Scaling Entropy (MSERRI1-4, MSERRI5-10, MSEResp1-4, MSEResp5-10), spectral coherence (CohRRI-Resp), cross DFA (ρ1 and ρ2) and cross MSE (XMSE1-4 and XMSE5-10) coefficients of RR and respiratory signal in four physiological conditions: supine, standing, supine with 0.1Hz breathing and standing with 0.1 Hz breathing. Main results: Body posture change is dominantly characterized by the change of RRI parameters, insensitivity of respiratory parameters, decrease of CohRRI-Resp and insensitivity of ρ1, ρ2, XMSE1-4 and XMSE5-10. Slow breathing in supination was characterized by the change of the linear and nonlinear parameters of both signals, reflecting the dominant vagal drive on RRI regulation and the impact of voluntary breathing on respiratory nonlinear parameters; CohRRI-Resp did not change with respect to supination, while ρ1 and ρ2 increased. Slow breathing in standing reflected the state of combined high sympathetic and parasympathetic drive both on linear and nonlinear RRI parameters, with striking influence on respiratory nonlinear parameters. With respect to supination with 0.1Hz breathing, CohRRI-Resp was unchanged, while with respect to standing, CohRRI-Resp was increased, pointing on the uppermost role of voluntary breathing on cardiorespiratory coupling in linear domain; XMSE1-4 decreased and XMSE5-410 increased, with respect to the values of standing position. Significance: This research provides a contribution to the framework of cardiorespiratory complexity exploration during supination/orthostasis and spontaneous/slow breathing. Body posture changes of the cardiopulmonary coupling pattern point on the higher order modalities of integrative cardiopulmonary mechanisms necessary for the adaptation of the organism. The volitional slow breathing has significant impact on that adaptability. Traditional and novel, proposed nonlinear parameters might be useful for evaluation of cardiorespiratory healthy state and for a new insight into neurocardiovascular pathology.